544 Evaluating global cosmetic regulatory frameworks using an adapted regulatory maturity benchmarking tool - Benjamin Ertl; Eunjoo Pacifici (Journal of Clinical and Translational Science)
Objectives/Goals: This research aims to modify an existing regulatory benchmarking framework, initially designed for medical products, to assess cosmetic product regulations in different countries. This tool will provide qualitative and quantitative comparisons of global regulatory approaches to cosmetics. Methods/Study Population: The World Health Organization’s global benchmarking tool (GBT) was selected as a suitable template for the adapted methodology. The GBT contains a comprehensive set of functions, indicators, and sub-indicators defining the high regulatory maturity standard. Although the 269 sub-indicators are tailored to the regulation of medical products, they can be intentionally adapted for other products. Relevant indicators specific to cosmetic regulation will be identified to construct a customized benchmarking tool. This tool will then be used to assess the regulatory maturity of selected countries and regulatory authorities, including the United States, the European Union, Japan, India, Brazil, China, Ethiopia, and Nigeria. Results/Anticipated Results: Preliminary analysis indicates a lack of harmonized standards for regulatory maturity across the global cosmetic market. The recent passage of the Modernization of Cosmetics Regulation Act of 2022 (MoCRA) has strengthened the United States’ regulatory framework, incorporating 11 of 13 adapted maturity indicators. The United States joins the European Union (10/13 indicators) and Japan (8/13 indicators) as leaders in cosmetic safety and manufacturing transparency. Common basic policies included good manufacturing practice regulations, while more advanced regulations cover adverse event reporting and premarket requirements. Discussion/Significance of Impact: Cosmetics, supplements, and homeopathic products lack transparency regarding safety and quality requirements. This project establishes a benchmark for cosmetic product regulation, addressing a historic gap in oversight. The benchmark supports regions with less developed regulatory policies to enhance cosmetic safety and quality standards.